Pentingnya Implementasi Pendidikan Karakter Di Sekolah Sebagai Implementasi Pembangunan Generasi Bangsa - Rezzahati, Ni Putu; Luwih, I Made (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The goal of character education is to instill morality, ethics, and religious values in pupils through science. Parents, instructors, and society all have a significant role in the creation and development of the participants' character. Every child has good potential from birth, but in order for each child's character to be created and developed to the fullest extent possible, that potential needs to be continuously refined and socialized. Children can also easily access digital media in this day and age. An era of digital technology that has both beneficial and negative effects Negative In order to help kids make the most of their digital media and reap positive effects for their lives, educators, parents, and adult society also have a responsibility to supervise and regulate what kids do with it.